Ergosterol purified from medicinal mushroom Amauroderma rude inhibits cancer growth in vitro and in vivo by up-regulating multiple tumor suppressors - Li, Xiangmin; Wu, Qingping; Xie, Yizhen; Ding, Yinrun; Du, William W.; Sdiri, Mouna; Yang, Burton B. (Oncotarget, 2015)
We have previously screened thirteen medicinal mushrooms for their potential anti-cancer activities in eleven different cell lines and found that the extract of Amauroderma rude exerted the highest capacity in inducing cancer cell death. The current study aimed to purify molecules mediating the anti-cancer cell activity. The extract of Amauroderma rude was subject to fractionation, silica gel chromatography,and HPLC. We purified a compound and identified it as ergosterol by EI-MS and NMR,which was expressed at the highest level in Amauroderma rude compared with other medicinal mushrooms tested. We found that ergosterol induced cancer cell death,which was time and concentration dependent. In the in vivo experiment, normal mice were injected with murine cancer cell line B16 that is very aggressive and caused mouse death severely. We found that treatment with ergosterol prolonged mouse survival. We found that ergosterol-mediated suppression of breast cancer cell viability occurred through apoptosis and that ergosterol up-regulated expression of the tumor suppressor Foxo3. In addition, the Foxo3 down-stream signaling molecules Fas, FasL,BimL, and BimS were up-regulated leading to apoptosis in human breast cancer cells MDA-MB-231. Our results suggest that ergosterol is the main anti-cancer ingredient in Amauroderma rude, which activated the apoptotic signal pathway. Ergosterol may serve as a potential lead for cancer therapy.